A phosphorous-based dendrimer targets mitochondria and normalizes the keratinocyte proliferation/differentiation balance to improve psoriasis - Emily Clement; Ranime Jebbawi; Abdelouahd Oukhrib; Hélène Labie; Maëlys Le Moal; Séverine Fruchon; Stéphanie Cassel; Anne-Marie Caminade; Cédric-Olivier Turrin; Muriel Blanzat; Michel Simon; Rémy Poupot (PLoS ONE, 2026)
Psoriasis vulgaris is a common chronic inflammatory skin disease associated with hyperproliferation and defective differentiation of keratinocytes. Despite new effective treatments using biologicals targeting key cytokines or their receptors, innovative therapeutic approaches remain to be discovered. Here, psoriasis-like imiquimod-induced skin lesions in mice were improved when topically treated with a nano-sized, phosphorus-based dendrimer capped with azabisphosphonate groups, so-called IMD-006, and previously known as ABP dendrimer. This effect was confirmed using ex vivo and in vitro human psoriasis models generated by adding T helper (Th)1-type and Th17-type inflammatory cytokines to skin explants and reconstructed epidermises, in which topically-applied IMD-006 normalized keratinocyte proliferation and differentiation. In 2D keratinocyte cultures, IMD-006 also decreased proliferation whilst promoting differentiation. It was internalized by keratinocytes and distributed to mitochondria. After treatment with IMD-006, changes to the morphology of the mitochondrial network, increases in mitochondrial ROS levels, and co-localization of mitochondria with lysosomes suggest it promotes mitochondrial degradation, a key step in keratinocyte differentiation. Therefore, our results show that IMD-006 could be a promising candidate for the topical treatment of psoriasis.